2015
DOI: 10.3389/fphar.2015.00283
|View full text |Cite
|
Sign up to set email alerts
|

Role of ErbB Receptors in Cancer Cell Migration and Invasion

Abstract: Growth factors mediate their diverse biologic responses (regulation of cellular proliferation, differentiation, migration and survival) by binding to and activating cell-surface receptors with intrinsic protein kinase activity named receptor tyrosine kinases (RTKs). About 60 RTKs have been identified and can be classified into more than 16 different receptor families. Their activity is normally tightly controlled and regulated. Overexpression of RTK proteins or functional alterations caused by mutations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
219
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(231 citation statements)
references
References 87 publications
3
219
0
1
Order By: Relevance
“…Many reports suggested PPARs modulation in cancer cells by either agonist or antagonist may be a potential treatment for metabolic diseases and cancer including BCa272829. Among those, the PPARγ pathway is particularly critical for the cancer stem cell properties of ErbB2-positive breast cancer cells3031, and has been reported to inhibit of ErbB activity in human breast cancer cells32.…”
mentioning
confidence: 99%
“…Many reports suggested PPARs modulation in cancer cells by either agonist or antagonist may be a potential treatment for metabolic diseases and cancer including BCa272829. Among those, the PPARγ pathway is particularly critical for the cancer stem cell properties of ErbB2-positive breast cancer cells3031, and has been reported to inhibit of ErbB activity in human breast cancer cells32.…”
mentioning
confidence: 99%
“…Studies have shown that growth factors such as EGF promote the proliferation of stem cells and maintain the balance of normal cells (27). EGFR is a member of the ErbB receptor family on the cell surface, which is involved in cellular processes, including proliferation, growth, migration and invasion (28). Studies have also found that EGFR adjusts EGF-mediated cancer cell proliferation through saliva acidification (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is a member of the ErbB receptor family on the cell surface, which is involved in cellular processes, including proliferation, growth, migration and invasion (28). Studies have also found that EGFR adjusts EGF-mediated cancer cell proliferation through saliva acidification (28,29). In addition, EGFR inhibitors were shown to induce cancer cells to express UL16 binding protein 1 in order to enhance their sensitivity to natural killer cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, the transition from noninvasive to invasive status is characterized by loss of the epithelial characteristics such as expression of cytokeratins and E-cadherin and gain of mesenchymal traits like vimentin, ibronectin and N-cadherin through a process that is known as epithelial to mesenchymal transition (EMT) [32]. EMT promotes cancer progression by allowing cancer cells to acquire invasive properties, to metastasize and also to acquire stem cell properties [33,34]. Interestingly, these cells that have acquired stem cell properties are characterized by increased expression of EMT genes, such as FoxC2, Zeb and N-cadherin [35,36].…”
Section: Role Of Erbb2 In Breast Cancer Invasion and Metastasismentioning
confidence: 99%